2015
DOI: 10.1186/s40409-015-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of human rabies in Henan province in China from 2005 to 2013

Abstract: BackgroundRabies is very common in People’s Republic of China. Henan province, in the central portion of China, is one of the most densely populated provinces in the entire country. With the new rabies epidemic trend noted in northern and western China, it is necessary to investigate the characteristics of human rabies in this area and control the disease.MethodsWe chose patients in hospital isolation in 18 municipalities in Henan province as the investigation subjects. Data were collected through systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
2
17
0
2
Order By: Relevance
“…In the current study, we found that more than four-fifths of animal bite victims applied no or inappropriate wound treatment, and similar findings have been reported in other national and international research [19, 34, 35]. Our analysis revealed that, most (66.6%) respondents could have an access to the RPC within 30 minutes, and nearly all victims (96.8%) could visit the RPC within 90 minutes.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, we found that more than four-fifths of animal bite victims applied no or inappropriate wound treatment, and similar findings have been reported in other national and international research [19, 34, 35]. Our analysis revealed that, most (66.6%) respondents could have an access to the RPC within 30 minutes, and nearly all victims (96.8%) could visit the RPC within 90 minutes.…”
Section: Discussionsupporting
confidence: 89%
“…Çalışmamızda, 6 yaş ve altındaki olgular ile 7 yaş üzerindeki olguların oranı hemen hemen aynıydı. Hem dünya genelinde hem de Türkiye'de yapılan çalışmalarda erkeklerde kuduz riskli temas daha sık görülmektedir (13)(14)(15)(16)18) . Bunun nedeni erkeklerin daha hareketli olup, dışarıda daha uzun süre vakit geçirmeleri olabilir.…”
Section: Discussionunclassified
“…According to previous studies, hundreds of pregnant women are exposed to injuries provoked by dog in China every year [ 10 , 11 ]. Nearly all patients in urban areas in China had received post-exposure prophylaxis (PEP) which was effective and safe.…”
Section: Discussionmentioning
confidence: 99%